The Study of Food Safety Awareness, Practices, and Perception Among CeDS Students in UTHM Pagoh - Abd. Rahman, Norfadhilah; Abd Razak, Nur Aleysa Shahira; Amat Azman, Puteri Nazatul Nisha; Sazeli, Zul Afiq (Multidisciplinary Applied Research and Innovation, 2025)
This study aims to examine the level of awareness among students of Centre for Diploma Studies (CeDS) at UTHM Pagoh towards food safety. Next, to identify their perception about food safety and hygiene in daily life, and to analyse the practices of the students about food safety as part of their daily routine. Descriptive analysis was used to analyse the research questions, and correlation analysis using SPSS was used to interpret the research output. The Krejcie and Morgan sampling method was used, involving 300 students as the sample size. This study used a randomly selected student sample (N = 325) from various diploma majors, out of the 2482 diploma students at UTHM. Primary data on food safety awareness, perception, and practices were collected through online questionnaires and generated using Google Forms. The results of this research indicate that there is a significant relationship between student knowledge about food safety, with correlations of 0.573, 0.661, and 0.682 between the different sections, all significant at a level are below 0.05.